“I know what to say now” Students’ evaluation and utilisation of Accidental Counsellor Training - Joanna E. Harnett; Claire E. Ashton-James; James Kite; Tonia Crawford; Sanetta H. J. du Toit; Leigh A. Wilson; Rosa Howard (PLoS ONE, 2025)
Introduction In 2020 and 2021, 280 health profession students who were engaged in student leadership roles and peer mentoring were invited to undertake extracurricular training in accidental counselling to build skills in recognising and responding to a person in distress. The aim of this study was to evaluate the acceptability of the online training course, and to explore students’ confidence to use Accidental Counsellor tools to support peers in distress after completion of the training course. Methods A retrospective cohort study including a post- intervention only design was used. A survey was administered approximately 12 months after 225 students completed an Accidental Counsellor training program. The survey instrument assessed reluctance or confidence to recognise and respond to someone having a mental health crisis, and acceptability of the training. Reliability coefficients were computed for scales, and descriptive analyses including frequencies and percentages were conducted using IBM SPSS Statistics (Version 27). Open-text responses underwent descriptive content analysis. Results Sixty-one students completed the online survey. Of these, 90% felt confident and 85% felt low reluctance to respond to peer mental health crises. Nearly all (85%) participants recognised at least one person in distress in the 12 months following the training. T-test confirmed no gender differences in mean confidence score (Men mean = 30.0, Std. dev. = 2.90; Women mean = 29.5, std. dev. = 4.80; t(63)=0.48, p = 0.633), however, there was a statistically significant difference between age groups as determined by one-way ANOVA (F(2,62)=7.43, p = 0.001). Listening non-judgmentally and referring the person to resources was the most common response to peer distress. The online format was described as offering accessibility and interaction benefits but lacked realism and engagement for some. Conclusion With ever increasing rates of depression and other mental health conditions being reported among university students, there is increasing pressure to develop strategies to support mental health and wellbeing. This project is unique in evaluating an online delivery of Accidental Counsellor training. Since completing the training, most participants recognized at least one person in distress and reported confidence and skill to respond.